Frei Germano de Annecy (1822-1890): lugares, saberes e práticas - Madi Filho, José Maurício Ismael (2022)
The research presents the life, work and teaching practices of Fray Germano of Annecy (1822-1890), a capuchin, born in Annecy, who lived in Brazil from 1858 to 1890. From 1858 to 1878, he was part of the teaching staff of the Episcopal Seminary of Sao Paulo. Thereafter he lived in the cities of Franca and Uberaba, respectively, and died in 1890 while attempting to return to his home country, France. Fray Germano was a Mathematics, Physics and Astronomy professor, as well as a sundial projector. He is considered being the pioneer of the Physics Department and was responsible for the weather and space observatories in the province of São Paulo, which led him to publish hundreds of meteorological bulletins and dozens of articles and notes about astronomical ephemeris.The question is: What were the knowledge and practices of Fray Germano of Annecy? This investigation seeks to know what and how he taught and what his scientific objects and instruments reveal about his scientific practices, as well as how he developed an aptitude for scientific taste and how his activities reveal the relationship between science and the Church in the 19th century. This research intersects the history of science and the education of science from a historical perspective. The discussions made by Le Goff and Dosse about this genre contribute to the construction of the theme, but the research relies particularly on the theoretical-methodological support arising from microhistory raised by authors such as Ginzburg and Levi. It also mobilized a wide and varied set of documents, such as documentation regarding the disciplinary formation of Savoia's Capuchin, articles published by the magazine of the Royal Academy of Chambéry, reports describing the classes available at the Episcopal Seminary, bureaucratic and personal documents regarding the mission of the Capuchins of Savoia in Brazil, photographs, engravings, letters, meteorological bulletins, publications on astronomical events, biographical reports and posthumous tributes to Fray Germano of Annecy.Besides the micro-history approach, this set of documents is analyzed based on historiographical discussions relevant to the history of science , science teaching and on theoreticalmethodological contributions referring to material culture and school material culture, present in authors such as Aubin, Besse, Braghini, Daston, Escolano Benito, Meloni, Munakata, among others